2018
DOI: 10.1111/hepr.13286
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive liver fibrosis assessment correlates with collagen and elastic fiber quantity in patients with hepatitis C virus infection

Abstract: Aim: Elastic fiber deposition is a cause of irreversibility of liver fibrosis. However, to date, its relevance to clinical features has not yet been clarified. This study aimed to clarify the correlation between non-invasive markers of fibrosis and fiber quantity, including elastic fiber, obtained from computational analysis.Methods: This retrospective study included 270 patients evaluated by non-invasive liver fibrosis assessment prior to liver biopsy. Of these patients, 95 underwent magnetic resonance elasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
(37 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, because the invasiveness of liver biopsy precludes repeated examinations, longitudinal assessment of hepatic fibrosis and steatosis is difficult. Recently, there have been several reports showing the utility of MRE‐based and MRI‐based PDFF for diagnosing hepatic fibrosis and steatosis . Imajo et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, because the invasiveness of liver biopsy precludes repeated examinations, longitudinal assessment of hepatic fibrosis and steatosis is difficult. Recently, there have been several reports showing the utility of MRE‐based and MRI‐based PDFF for diagnosing hepatic fibrosis and steatosis . Imajo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance elastography (MRE) is a magnetic resonance imaging (MRI)‐based method for quantitative imaging of tissue stiffness. MRE has been reported to be a useful method for diagnosing fibrosis in patients with chronic liver disease . In addition, proton density fat fraction (PDFF) measurement is an MRI‐based method for quantitative assessment of hepatic steatosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported the accuracy of magnetic resonance elastography and proton density fat fraction to be superior to TE in CLD. [39][40][41][42][43] Increasing availability of non-invasive diagnostic technology is beneficial for CLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The application of computer‐assisted quantitative analysis revealed that the pattern of liver fibrosis progression in NAFLD was different from that of chronic HCV infection: a striking difference was observed in fiber accumulation between Brunt's fibrosis stages F3 and F4 in NAFLD, in contrast to the somewhat linear association observed in chronic HCV infection . Moreover, the ranges of collagen and elastin levels in F4 stage NAFLD were larger than for stages F1–3 .…”
Section: Assessment Of Liver Fibrosismentioning
confidence: 95%